2021
DOI: 10.1039/d1tb01236c
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polyurethane nerve guide conduits with different moduli influence axon regeneration in transected peripheral nerve injury

Abstract: Nerve guide conduits (NGCs) can replace autogenous nerve grafting in the treatment of peripheral nerve system (PNS) injury. However, the modulus of the polyurethane NGCs that affects the outcome of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…This result agreed with our previous study, which showed that the mechanical properties significantly influenced PNS regeneration. 20 In summary, the in vitro study showed that BWPU-DSC NGCs, especially B50%–DSC50% scaffold NGCs, could dramatically promote the proliferation and extension of cell processes in ex vivo culture.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This result agreed with our previous study, which showed that the mechanical properties significantly influenced PNS regeneration. 20 In summary, the in vitro study showed that BWPU-DSC NGCs, especially B50%–DSC50% scaffold NGCs, could dramatically promote the proliferation and extension of cell processes in ex vivo culture.…”
Section: Resultsmentioning
confidence: 89%
“…In our previous study, BWPU NGCs showed complete nerve regeneration 12 weeks post-implantation. 20 In this study, we set the end of the experiment 6 weeks earlier to better observe the effect of BWPU-DSC NGCs in the repair of PNS. Our results indicated that BWPU-DSC NGCs dramatically increased the effect of sciatic nerve regeneration; at 6 weeks post-implantation, the BWPU-DSC NGC-implanted group showed obvious connected regenerated nerves in the scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of tissue engineering, polyurethane (PU) scaffolds have attracted much attention and effectively promote the proliferation of macrophages, regulate the polarization of macrophages to the M2 type, promote the adhesion and proliferation of endothelial cells, and promote tissue and vascular regeneration. The final properties of polyurethane significantly depend on the monomer used, and the biocompatible lysine-based isocyanate and poly­(ethylene glycol) (PEG) are two acclaimed components of PU. For example, the biodegradable lysine-derived polyurethane adhesive TissuGlu was approved by the US FDA in 2014 for use as a tissue adhesive in surgical operations, and it has been used in research in the fields of nerve repair, vascular reconstruction, and cartilage regeneration. In addition, based on our previous works, , a series of waterborne polyurethanes were prepared using l -lysine ethylester diisocyanate (LDI), 1,3-propanediol (PDO), and l -lysine as hard segments and poly­(ε-caprolactone) (PCL) and PEG as soft segments. These waterborne polyurethanes showed excellent biological characteristics for the regeneration of soft tissues. , It is speculated that the application of a hybridized biomaterial combining lysine-based polyurethane with HA to treat VF injuries can promote cell proliferation and regulate the polarization of macrophages to the M2 type, thus promote the regeneration of in situ blood vessels, and inhibit scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the biodegradable lysine-derived polyurethane adhesive TissuGlu was approved by the US FDA in 2014 for use as a tissue adhesive in surgical operations, and it has been used in research in the fields of nerve repair, vascular reconstruction, and cartilage regeneration. In addition, based on our previous works, , a series of waterborne polyurethanes were prepared using l -lysine ethylester diisocyanate (LDI), 1,3-propanediol (PDO), and l -lysine as hard segments and poly­(ε-caprolactone) (PCL) and PEG as soft segments. These waterborne polyurethanes showed excellent biological characteristics for the regeneration of soft tissues. , It is speculated that the application of a hybridized biomaterial combining lysine-based polyurethane with HA to treat VF injuries can promote cell proliferation and regulate the polarization of macrophages to the M2 type, thus promote the regeneration of in situ blood vessels, and inhibit scar formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation